Relation between baseline risk and treatment decisions in non-ST elevation acute coronary syndromes: an examination of international practice patterns. Issue 7 (14th June 2005) - Kaul, P; Newby, L K; Fu, Y; Mark, D B; Goodman, S G; Wagner, G S; Harrington, R A; Granger, C B; Van de Werf, F; Ohman, E M; Armstrong, P W
Abstract : Objectives: To examine the interaction between ST segment depression on the baseline ECG and subsequent in-hospital revascularisation on six month mortality among patients with non-ST elevation acute coronary syndromes. To examine whether ST segment depression influenced clinical decision making and whether there was international variation in the use of cardiac procedures across ST segment depression categories. Methods: 11 453 patients enrolled in GUSTO-IIB (global use of strategies to open occluded coronary arteries), PARAGON (platelet IIb/IIIa antagonism for the reduction of acute coronary syndrome events in a global organisation network) -A, and PARAGON-B were studied. Patients were categorised as having no ST segment depression, 1 mm ST segment depression in two contiguous leads, and ST segment depression ⩾ 2 mm in two contiguous leads. International practice across four geographic regions was examined: USA, Canada, Europe, and Australia/New Zealand. Results: Revascularisation appeared to have no impact on survival among patients with no ST segment depression; however, revascularisation was associated with a significant survival benefit among patients with ST segment depression ⩾ 1 mm. There was an inverse relation between the extent of ST segment depression and the use of angiography as well as angioplasty (p < 0.01). However, patients with ST segment depression ⩾ 2 mm were more likely to undergo bypass surgery. The only significant trend of increasing use of revascularisation procedures with increasing ST segment depression was observed in the USA. Conclusions: International practice patterns in procedure use appear to be insensitive to the extent of ST segment depression. Major opportunities for more efficient delivery of care exist in all regions.